Institutions and Culture: Thorstein Veblen’s and Pierre Bourdieu’s economic thought in dialogue - Valiati, Leandro; Fonseca, Pedro Cezar (Iberian Journal of the History of Economic Thought, 2014)
This article aims to explore elements of economic thought present in Thorstein Veblen and Pierre Bourdieu from the perspective of the History of Economic Thought. These two authors, from distinct fields of analysis, produced in their theories common analytical tools that may be appropriate to understand the influence of cultural aspects in the economic process, especially when considering the concepts of habits, institutions, symbolic profit, social distinction and conspicuous consumption. In this perspective, the paper proposes to conduct an analysis of the historical and theoretical thinking of these authors, so compared in order to detect the main points of contact in their understanding of how cultural value and its institutions influence patterns of economic consumption within a society.